Insensitivity to loss predicts apathy in huntington's disease. Issue 9 (30th July 2019) - McLauchlan, Duncan J.; Lancaster, Thomas; Craufurd, David; Linden, David E.J.; Rosser, Anne E.
Abstract: Background: Apathy is a deficit in goal‐directed behavior that significantly affects quality of life and function. It is common in Huntington's disease and other disorders affecting corticostriatal pathways. Deficits in processing of reward, altered effort, and executive dysfunction are associated with apathy in other disorders, but the cognitive processes leading to apathy in Huntington's disease remain largely unknown. A previously reported deficit in learning from losses in Huntington's disease raises the possibility of a hitherto unrecognized mechanism leading to apathy. This study's objective was to delineate the cognitive processes associated with apathy in HD. Methods: We tested 51 Huntington's disease participants and 26 controls on a battery of novel and established measures to assess the contribution to apathy in Huntington's disease of executive function, reward value, reward‐effort calculations, instrumental learning, and response to reward and loss. Results: Huntington's disase participants had deficits in instrumental learning with impaired response to loss, but no evidence to suggest altered reward‐related behavior or effort. We also saw an executive dysfunction contribution to apathy in Huntington's disease. Discussion: We report the novel finding that apathy in Huntington's disease is associated with blunted responses to losses and impaired instrumental learning. This association is consistent with the known early degeneration of the indirect pathway and amygdala involvement in apathy in Huntington's disease, but is previously unreported in any disorder. In keeping with the comparative preservation of the ventral striatum and orbitofrontal cortex in Huntington's disease, reward valuation and reward‐effort calculations did not contribute to apathy. © 2019 International Parkinson and Movement Disorder Society